The Effect of Food Intake on the Incidence of Malnutrition in Toddlers in the Work Area of the Kertosari Health Center, Banyuwangi Regency - Endang Sri Purwanti Wulandari; Erma Sulistyaningsih; Ancah Caesarina Novi Marchianti (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aims to determine the effect of food intake patterns on malnutrition incidence in toddlers in the working area of Kertosari Health Care. This study used a cross-sectional method with a research population of 30 toddlers. The data were obtained from validated questionnaires and food intake measurements using a 24 hours food recall form. Samples in this study as many as 30 malnourished toddlers and spread in the Kertosari Health Care working area. The data were analyzed using descriptive analysis techniques and ordinal logistic regression influence tests. The results of the study showed that energy intake patterns (p = 0.032), protein intake patterns (p = 0.026), fat intake patterns (p = 0.026), carbohydrate intake patterns (p = 0.014), zinc intake patterns (p = 0.043) and calcium intake patterns (p = 0.026) with the incidence of malnutrition in toddlers